2009
DOI: 10.1021/bi9003952
|View full text |Cite
|
Sign up to set email alerts
|

Novel Domain Arrangement in the Crystal Structure of a Truncated Acetyl-CoA Synthase from Moorella thermoacetica,

Abstract: Ni-dependent Acetyl-CoA synthase (ACS) and CO dehydrogenase (CODH) constitute the central enzyme complex of the Wood-Ljungdahl pathway of acetyl-CoA formation. The crystal structure of a recombinant bacterial ACS lacking the N-terminal domain that interacts with CODH shows a large reorganization of the remaining two globular domains, producing a narrow cleft of suitable size, shape and nature to bind CoA. Sequence comparisons with homologous archaeal enzymes that naturally lack the N-terminal domain show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
2
9
0
1
Order By: Relevance
“…Interestingly, the A cluster activities of the proteins correlated with the type of signal observed, in that only samples that displayed type I signals (ACS Ch and the ACDS complex) were able to carry out significant carbonyl exchange activity. Recent crystallographic analyses on an N-terminally truncated form of ACS from M. thermoacetica indicated that a substantial reorientation of the relative positions of the central and C-terminal domains had taken place, as compared with either the closed or open forms of the protein where some degree of contact with the N-terminal region is always maintained (50). Thus, the change in the EPR signal from type I to type II is seen to take place in parallel with the conformational changes that result from loss of interactions of the N-terminal domain with the central and C-terminal domains in ACS or in the case of the ACDS complex with the loss of contact of the ␤ subunit with other protein components in the complex such as the ␣ 2 ⑀ 2 CO dehydrogenase subcomponent.…”
Section: Epr Features Correlated With Different Catalytic Properties mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the A cluster activities of the proteins correlated with the type of signal observed, in that only samples that displayed type I signals (ACS Ch and the ACDS complex) were able to carry out significant carbonyl exchange activity. Recent crystallographic analyses on an N-terminally truncated form of ACS from M. thermoacetica indicated that a substantial reorientation of the relative positions of the central and C-terminal domains had taken place, as compared with either the closed or open forms of the protein where some degree of contact with the N-terminal region is always maintained (50). Thus, the change in the EPR signal from type I to type II is seen to take place in parallel with the conformational changes that result from loss of interactions of the N-terminal domain with the central and C-terminal domains in ACS or in the case of the ACDS complex with the loss of contact of the ␤ subunit with other protein components in the complex such as the ␣ 2 ⑀ 2 CO dehydrogenase subcomponent.…”
Section: Epr Features Correlated With Different Catalytic Properties mentioning
confidence: 99%
“…Of course, those residues are absent in the isolated ␤ subunit, but the possible locations of functionally equivalent residues in the ACDS complex have been postulated from a recent structural alignment analysis of the ACS Mt N-terminal domain with regions of the archaeal ␣ subunit from the M. barkeri ␣ 2 ⑀ 2 enzyme (50), and a sufficiently high structural similarity was found for the authors to propose a model of the region of the CODH ␣ subunit that may interact with the ␤ subunit. In that model, conserved or invariant residues could provide 31 of the total 41 contacts made within 3.8 Å between the N-and the C-terminal domains in the closed form (50). Two residues in the ACS Mt N-terminal domain, Ile-146 and Val-149 (which would correspond to M. barkeri CODH ␣ subunit Leu-507 and Val-510), are in particularly close proximity to the A cluster.…”
Section: Possibility Of a Direct Steric Effect In Coordination Geometrymentioning
confidence: 99%
“…According to the paramagnetic mechanism, CO accesses the A-cluster via a channel [ 16 ] and can bind to Ni p to form a Ni(I)-CO species, which upon reduction accepts an additional methyl group, so that subsequent C-C bond formation and S-C coupling with a CoA molecule finally yields acetyl-CoA [ 6 , 14 , 21 24 ]. The influence of the N-terminal and middle ACS domains on the function of the A-cluster has remained a matter of debate [ 14 , 17 , 25 , 26 ]. Interestingly, acetyl-CoA synthesis activity of ACS under in vitro conditions depends on the relative CO concentration.…”
Section: Introductionmentioning
confidence: 99%
“…[1,4,[8][9][10] In the meantime, a consensus has been reached that HSCoA is the last substrate to bind. [10,11] It is also widely accepted that the resting state contains both Ni centers in the oxidation state +II, and that Ni d mainly serves the stabilization of the structure. Reduction of Ni p , either to Ni I or even to Ni 0 , produces the active state that is capable of creating the acetyl moiety from CO and a methyl species.…”
mentioning
confidence: 99%